Gastropoda Diversity in the Coastal Area of Kapas Island, Tolitoli, Central Sulawesi - Sari, Retno; Fitrallisan, Fitrallisan; Hardini, Erza Shafiah Zahraani Pravita; Lemako, Gideon Sulivan; Patigu, Rosy Feraningsih (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Kapas Island is one of the coastal tourist destinations that has a panorama of white sand with various types of plants and marine animals. Types of marine animals that are also found in coastal areas are gastropods. One measure of the biological system's sustainability is species diversity. The purpose of this study is to examine the gastropod diversity in the coastal region of Kapas Island, Tolitoli, Central Sulawesi. According to the findings of environmental parameter tests, temperatures with different substrates ranged from 29.3 °C to 32.6 °C, salinity from 33 to 38 ppt, and pH from 7.88 to 8.07. The types of Gastropods found in the study amounted to 34 species, from 26 Genus, 17 Families with 6 Orders and 2 subclasses. The Diversity Index Analysis's (H') total value for the Medium diversity category was 2.61, with findings ranging from 1.52-2.29. While the Evenness Index (E) rating ranges from 0.5 to 0.76, the medium-high evenness category's overall analysis value is 0.74. The dominance index (D) data showed no dominance amongst species, with a total index value of 0.1 and a range of 0.14 to 0.37. These results indicate that gastropods in the coastal area of ​​Kapas Island have moderate diversity and are evenly distributed. There is no dominance between species, which indicates that the gastropod community is stable with favorable environmental conditions.